Men at home, men and home in two Anglophone novels by Indian women writers. Issue 7 (2nd July 2016) - Mirza, Maryam
Abstract: Postcolonial Indian women novelists writing in English have been deeply concerned with addressing the ways in which 'home' in patriarchal societies is an ambiguous space, characterized by unequal gender relationships that make it a terrain rife with violence, and feelings of alienation and discontent for women. Through the lens of two contemporary Anglophone novels by Indian women writers, Arundhati Roy's (1997) The God of Small Things and Manju Kapur's (2006) Home, this article evaluates the significance of the relationship between male identities, politics and domestic spaces in India. Focusing primarily on two bourgeois male characters, Estha and Vicky, the article examines, in depth, their painful coming-of-age in terms of the complex intersection of gender, class and age hierarchies in the domestic arena and demonstrates the centrality of the concept of home to their sense of self and space.